DEVELOPMENT OF COMICS BASED LEARNING MEDIA IN CLASS 2 THEME 5 MATERIAL MY EXPERIENCE AT HOME - Destriana; Dian Nuzulia Armariena; Marleni (Esteem Journal of English Education Study Programme, 2024)
This research is motivated by the low interest in reading of students in learning Indonesian because in the teaching and learning process teachers tend to use tools in the form of media in the form of books only and lecture methods, making it less interesting for students to pay attention to. This research aims to determine the development of comic-based learning media that is valid, practical and effective for use in class 11 in Indonesian language subjects. This research was carried out at SD Negeri 17 Palembang which is located on Jl. Enim Lorok Pakjo, Demang Lebar Daun, Palembang City, South Sumatra. This research is a type of ADDIE research, namely analysis, design, development, implementation and evaluation. The population and sample in this research were class 2 students at SD Negeri 17 Palembang, totaling 30 students in the class. Data collection techniques in this research are observation, interviews, questionnaires and documentation. , The results of this research are the results of the assessment of all validators, the percentage is 98% with the criteria "Very Valid" while one to one gets an average percentage of 84.5%. It can be concluded very practically, based on the criteria, the average percentage value is 81%-100 % that the comic media developed is very practical, the implementation of the Small Group trial phase obtained an average percentage of 90.7% Very Practical. The results of the data analysis of the Flied test product trial carried out by 30 class 2 students at SD Negeri 17 Palembang in the table show that It can be seen that the students' response to the total score was obtained with a percentage of 92.2% with very practical criteria, the potential effect on the 2nd class students at SD Negeri 17 Palembang, totaling 30 students, through 10 multiple choice test questions with a completion percentage of 86% or 27 students achieved the KKM score and 3 students below the KKM. Based on this percentage, the potential effect and final results or post test with a percentage result of 90% (p≥80%) so that comic media is categorized as very potential.